Comparison of Neonatal Transport Scoring Systems and Transport-Related Mortality Score for Predicting Neonatal Mortality Risk. Issue 2 (February 2015) - Sutcuoglu, Sumer; Celik, Tugce; Alkan, Senem; Ilhan, Ozkan; Ozer, Esra Arun
Abstract : Objectives: To predict the risk of mortality of neonates, birth weight and gestational age were previously used. However, these criteria were considered inadequate; therefore, various scoring systems have been developed in the recent years. The aim of the study was to evaluate the performance of predicting mortality by Mortality Index for Neonatal Transportation (MINT), Score for Neonatal Acute Physiology-Perinatal Extension II (SNAP-PE-II), and Transport Related Mortality Score (TREMS). Methods: All infants transferred to the neonatal intensive care unit between January 1 and December 31, 2011, were included. The scores of SNAP-PE-II, MINT, and TREMS of the all cases were calculated. TREMS is our proposed scoring system and it consists of 5 variables (hypoglycemia, hypoxia, hypercarbia, hypotension, and hypothermia). The scoring systems, SNAP-PE-II, MINT, and TREMS, were compared in terms of mortality risk. Results: A total of 306 newborn infants constituted the study population. The mean gestational age was 33.1 ± 5 weeks and the mean birth weight was 2031.2 ± 1018 g, and 183 (59%) babies were male. The sensitivity of MINT score for predicting mortality was higher than SNAP-PE-II and TREMS. However, specificity was higher in TREMS score. The negative predictive value was highest in MINT score, whereas TREMS has the highest positive predictive value. Conclusions: The TREMS scoring system is a simple scoring system with a high specificity for predicting mortality. Further studies with larger sample size including more centers and newborn infants with diverse clinical problems are needed to assess the validity and reliability of the TREMS scoring system.